Government Policy Analysis to Develop the Krian-Manyar-Gresik Toll in order to Reduce Traffic Jam using A Dynamic System Approach - sukma, dwi; Nugraha, Isna; Rahmawati, Nur; Syamsiah, Yuliatin Ali; Alfani, Ahmad Mujaddid (Universitas Muhammadiyah Sidoarjo, 2022)
Infrastructure development in an area, including the construction of toll roads, is aimed at developing a region and increasing the economy of the region. The construction of the toll road which is connected from Krian-Manyar-Gresik is carried out to facilitate traffic connecting the two cities. Traffic jams often occur at the link between the two cities. Congestion that occurs is usually caused by an increase in the volume of vehicles. Therefore, the construction of a toll road connecting the two cities is the best alternative. This research aimed to know government policies effectiveness in the construction of this toll road. The method used in this research is to use a dynamic system approach. From the results of the traffic simulation model design, it is found that the construction of toll roads is considered very influential and can be a way out of congestion problems. This is due to a decrease in the degree of saturation of congestion and although there is an increase from year to year, it is only slightly and not too significant. So the researchers suggest to continue the planned toll road construction project.